2014
DOI: 10.1016/j.ypmed.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Healthy Dads, Healthy Kids’ community randomized controlled trial: A community-based healthy lifestyle program for fathers and their children

Abstract: HDHK significantly improved health outcomes and behaviors in fathers and children, providing evidence for program effectiveness when delivered in a community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
188
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(206 citation statements)
references
References 61 publications
13
188
2
3
Order By: Relevance
“…These findings are consistent with other group-based group weight loss programs [22,23]. "Healthy Dads, Healthy Kids," a community randomized controlled trial, highlighted significant community-based healthy lifestyle intervention effects for fathers' weight loss [22]. Leahey et al (2014) found that weight loss was enhanced with optional group sessions [24].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These findings are consistent with other group-based group weight loss programs [22,23]. "Healthy Dads, Healthy Kids," a community randomized controlled trial, highlighted significant community-based healthy lifestyle intervention effects for fathers' weight loss [22]. Leahey et al (2014) found that weight loss was enhanced with optional group sessions [24].…”
Section: Discussionsupporting
confidence: 77%
“…A similar percentage of women in HW and SOH lost 5% or more of their body weight (22.5% and 19.7%, respectively) [12]. These findings are consistent with other group-based group weight loss programs [22,23]. "Healthy Dads, Healthy Kids," a community randomized controlled trial, highlighted significant community-based healthy lifestyle intervention effects for fathers' weight loss [22].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Parent-only treatment has also been found superior to (Munsch et al, 2008), and noninferior to traditional parent and child FBT, and improved effects were shown with a parent-centered dietary intervention (Collins et al, 2011;Okely et al, 2010). Parent-only approaches have been found superior to waitlist control conditions (Bean et al, 2012;Jansen et al, 2011, Moens & Braet, 2012, including a fatheronly treatment (Morgan et al, 2014), and favorable outcomes have been shown with a predominantly African American population (Mazzeo et al, 2014). It is particularly effective when added to a lifestyle program (Golley et al, 2007), and the addition of parent skills training to behavioral programs (Magarey et al, 2011) and FBT (Israel et al, 1985) appear to bolster efficacy of treatments.…”
Section: Parent-only Behavioral Treatmentmentioning
confidence: 99%
“…This approach emphasizes the importance of parental modeling and authority over the home environment (Golan & Weizman, 2001), as well as engaging the parents as agents of change (Apter, Fainaru, Golan, & Weizman, 1998). Parent-only approaches have been tested in 14 trials included in this review (Apter et al, 1998;Bean, Wilson, Thornton, Kelly, & Mazzeo, 2012;Collins et al, 2011;Golan & Crow, 2004;Golan, Kaufman, & Shahar, 2006;Golley, Magarey, Baur, Steinbeck, & Daniels, 2007;Janicke et al, 2008;Jansen, Mulkens, & Jansen, 2011;Magarey et al, 2011;Mazzeo et al, 2014;Moens & Braet, 2012;Morgan et al, 2014;Munsch et al, 2008;Okely et al, 2010;Shelton et al, 2007). In two trials, Golan and colleagues found FBT with parents as the agents of change more effective than FBT with children as the agents of change for both children (Golan et al, 2006) and adolescents (Apter et al, 1998), with the parentfocused treatment remaining superior at 7-year follow-up (Golan & Crow, 2004), although it should be noted that this study was conducted within a different region and culture (Israel with two-parent families).…”
Section: Parent-only Behavioral Treatmentmentioning
confidence: 99%